Role of computed tomographic scanning of the thorax prior to bronchoscopy in the investigation of suspected lung cancer. Issue 5 (1st May 2000) - Laroche, Clare; Fairbairn, Ian; Moss, Hilary; Pepke-Zaba, Joanna; Sharples, Linda; Flower, Chris; Coulden, Richard
Abstract : BACKGROUND: Fibreoptic bronchoscopy (FOB) is the usual initial investigation of choice in patients with suspected endobronchial carcinoma, but it is often non-diagnostic. Once a positive diagnosis has been made, many patients undergo staging by computed tomographic (CT) scanning to assess the extent of the disease and its suitability for radical treatment. To determine whether initial CT scanning before FOB is a cost effective way of reducing subsequent unnecessary or unhelpful invasive diagnostic procedures, a study was undertaken in 171 patients with suspected endobronchial carcinoma. METHODS: A randomised two group study was performed with all patients undergoing an initial CT staging scan. In group A the CT scans were reviewed before FOB, allowing cancellation or a change to an alternative invasive procedure if considered appropriate. In group B all patients proceeded to FOB with the bronchoscopist blinded to the result of the CT scan until after the procedure. RESULTS: In group A six of 90 patients (7%) required no further investigations as the CT scan was either normal, consistent with benign disease, or consistent with widespread metastatic disease. Of the remainder, bronchoscopy was diagnostic in 50 of 68 (73%) in group A compared with 44 of 81 (54%) in group B (p = 0.015). Overall, a positive diagnosis was made after a single invasive investigation in 64 of 84 patients (76%) in group A compared with only 45 of 81 patients (55%) in group B (p = 0.005). Only seven of 90 patients (8%) in group A required more than one invasive investigation compared with 15 of 81 patients (18.5%) in group B. In patients with malignancy, bronchoscopy was more likely to be diagnostic in group A (50 of 56 patients (89%)) than in group B (44 of 62 (71%); p = 0.012), and the diagnosis was more frequently made on the initial invasive investigation (group A, 63 of 70 (90%); group B, 44 of 62 (71%); p = 0.004). Because of the lower number of invasive procedures performed in group A than in group B, the cost of performing CT scans before FOB in all patients in group A would have equated to a projected cost of performing CT scans in 60% of patients after FOB in group B. CONCLUSIONS: Performing initial CT thoracic scans before bronchoscopy in patients with suspected endobronchial malignancy is a cost effective way of improving diagnostic yield from invasive diagnostic procedures and occasionally may obviate the need for any further investigation.